Analysis of camera orientation variation in airborne photogrammetry: images under tilt (roll-pitch-yaw) angles - B. Ruzgienė (Journal of Measurements in Engineering, 2014)
Taking images for airborne photogrammetry, tilt angles (drifts) variations of camera are resulting to objects positions on the images therefore influence to correctness and accuracy of produced geodata. Several experiments have been done for investigation of camera’s roll-pitch-yaw angles determination regarding to technical flying means orientation in the space. Using aerial triangulation technique, exterior orientation parameters of each image from entire flight strip – projection center coordinates and image tilt angles with estimated accuracy are presented. Results show coincidences or discrepancies to requirements specified in aerial photography regulations. In order to investigate deflections of camera’s tilts, stereo pair of images has been processed using airborne photogrammetric approach and different software. Two digital photogrammetric software (DDPS and LISA PHOTO) used in experimental image orientation operates on particular algorithms. Determined values of exterior orientation parameters differ not significantly. Exterior orientation of images gained by Unmanned Aerial Vehicle (UAV) with mounted CCD camera has been done. As shows analysis, images from UAV Photogrammetry are under marketable tilts. Using a certain number of Ground Control Points (GCP) measured by GPS, exterior orientation was not possible; the results not meet the accuracy requirements.